Analysis of the cutting fluid influence on the deep grinding process with a CBN grinding wheel - Fusse, Ronaldo Yoshinobu [UNESP] (2004)
The application of cutting fluid in a deep grinding process is becoming more and more important, mainly where the cutting fluids are used as an external agent to the grinding conditions. The role of the fluid in grinding operations is in refrigeration of the workpiece, removal of the shavings, lubrication of the grinding zone, and refrigeration and cleaning of the wheel. The efficiency of a cutting fluid will depend mainly of the type of fluid that will be used. In this work, the influences of the type of cutting fluid used in a deep grinding process of the steel VC131 using CBN grinding wheel are analyzed. Three different types of cutting fluids were used: a vegetable emulsion, a synthetic solution and a integral oil. The variables analyzed during and after the grinding process were the grinding force, the superficial roughness, the acoustic emission (EA), the temperature of the piece and the G ratio (relationship between the volume of material removed from the piece and the volume worn off the grinding wheel). The integral oil showed the best performance relative to the following output variables: EA, cutting force and G ratio. The vegetal emulsion was the fluid that best dissipated heat from the cutting region.